Catastrophic health expenditure among single empty-nest elderly with multimorbidity in rural Shandong, China: the effect of co-occurrence of frailty - Zhengyue Jing; Jie Li; Pei Pei Fu; Yi Wang; Yemin Yuan; Dan Zhao; Wenting Hao; Caiting Yu; Chengchao Zhou (BMC, 2021)
Abstract Background Previous studies have indicated that older adults with multimorbidity had higher risk of incurring catastrophic health expenditure (CHE). However, the effect of co-occurrence of frailty on CHE among single empty-nest elderly with multimorbidity remains unclear. This study aims to explore the effect of co-occurrence of frailty on CHE among single empty-nest elderly with multimorbidity, and whether this effect is moderated by economic status. Methods A cross-sectional household survey of the older adults in 2019 in Shandong province, China. A total of 606 single empty-nest elderly aged 60 years or older were included in this study. CHE was defined as the out-of-pocket payments for health care that equals or exceeds 40% of the household' s capacity to pay. Logistic regression models are employed to examine the effect of co-occurrence of frailty on CHE among single empty-nest elderly with multimorbidity. The interaction term is introduced to explore the economic status difference in this effect. Results The CHE incidence for single empty-nest elderly with multimorbidity alone is 64.2%, and the co-occurrence of frailty results in an increase by almost 1.3 times (84.0%) in CHE incidence among single empty-nest elderly with multimorbidity. The co-occurrence of frailty increases the risk of incurring CHE among the single empty-nest elderly with multimorbidity, with the odds of incurring CHE increased by 3.19 times (OR = 3.19; P = 0.005). Furthermore, the interaction analysis shows that the effect of co-occurrence of frailty on CHE among single empty-nest elderly with multimorbidity still exist in lower economic status groups (OR = 4.64; P = 0.027), but not in higher economic status (OR = 2.76; P = 0.062). Conclusions This study demonstrates that there is a positive effect of co-occurrence of frailty on the CHE among the single empty-nest elderly with multimorbidity, and this effect varies by economic status. The health policy-makers should reorganize the healthcare system to make it pro-poor, so as to meet the multiple medical demand and reduce the potential economic burden and inequalities of older adults.